2019
DOI: 10.24251/hicss.2019.870
|View full text |Cite
|
Sign up to set email alerts
|

How to connect design thinking and cyber-physical systems: the s*IoT conceptual modelling approach

Abstract: The alignment of enterprise models and information systems is a factor that influences the efficiency of enterprise practices. Considering the changing landscape in the age of the fourth industrial revolution, it is imperative that alignment methodologies are evolved with the progression of enterprise models and the transformation from information systems to cyber-physical systems (CPSs). This issue was dissected in three layers-scenario layer, modelling layer, and run-time environment. In this structure, desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…When it comes to innovation ecosystems and open perspectives, the novel paradigms of Industry 5.0 (Carayannis et al, 2021; EU Report on Industry 5.0, 2021) and Society 5.0 (Onday, 2019;Fukuyama, 2018) can be considered as the answer to the demand of a renewed human-centered/human-centric industrial paradigm, starting from the (structural, organizational, managerial, knowledge-based, philosophical, and cultural) reorganization of the production processes to then generate positive implications first within the business perspectives and secondly towards all the components belonging to the ecosystem. Several scholars (Fauquex et al, 2015;Vitali et al, 2017;Taratukhin et al, 2018;Nahavandi, 2019;Walch & Karagiannis, 2019) have emphasized the importance and role of modifying the innovation management framework with a focus on human/user centeredness. For instance, Skobelev and Borovik (2017) and Ozdemir and Hekim (2018) have discussed the role and importance of I5.0, which is more human-centered as compared with Industry 4.0 (I4.0) just because I5.0 helps to connect open innovation and technological policies with the overall corporate strategy of the firms, thus creating a suitable environment and ecosystem.…”
Section: The Need For Industry and Society 50 Approaches To Decisionmentioning
confidence: 99%
“…When it comes to innovation ecosystems and open perspectives, the novel paradigms of Industry 5.0 (Carayannis et al, 2021; EU Report on Industry 5.0, 2021) and Society 5.0 (Onday, 2019;Fukuyama, 2018) can be considered as the answer to the demand of a renewed human-centered/human-centric industrial paradigm, starting from the (structural, organizational, managerial, knowledge-based, philosophical, and cultural) reorganization of the production processes to then generate positive implications first within the business perspectives and secondly towards all the components belonging to the ecosystem. Several scholars (Fauquex et al, 2015;Vitali et al, 2017;Taratukhin et al, 2018;Nahavandi, 2019;Walch & Karagiannis, 2019) have emphasized the importance and role of modifying the innovation management framework with a focus on human/user centeredness. For instance, Skobelev and Borovik (2017) and Ozdemir and Hekim (2018) have discussed the role and importance of I5.0, which is more human-centered as compared with Industry 4.0 (I4.0) just because I5.0 helps to connect open innovation and technological policies with the overall corporate strategy of the firms, thus creating a suitable environment and ecosystem.…”
Section: The Need For Industry and Society 50 Approaches To Decisionmentioning
confidence: 99%
“…Innovation will be implemented only through human/user-centered financially viable and marketable products. Moreover, [20] concluded that, with the emergence of IoT and Industry 5.0 concepts, the proper alignment of enterprise model (business model) and information systems, together with the alignment of physical and cyberspace, is very important for making innovation implementable. [21] also stated that IoT devices and products should be "people-aware" and should be driven by user needs instead of technological advancements, and design thinking mindsets, processes, tools, and techniques are crucial for what they called "people-aware" IoT applications and products.…”
Section: Fifth Phasementioning
confidence: 99%
“…[60,61] Define the wicked problem as a complex and open-ended challenge and offer design thinking as a solution. [4,5,7,20,21,50] have emphasized the importance and role of design thinking for modifying the innovation management framework and creating an ecosystem for the IoT and Industry 5.0 era with a focus on human/user centeredness. Similarly, [7][8][9]11] discuss the role and importance of design thinking in Industry 5.0, which is more human-centered as compared to Industry 4.0.…”
Section: Design Thinking-the Missing Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully clarify the research intention of the analysis, we utilize material from the scientific field of Conceptual Modeling [13] Conceptual representations help in the analysis of the current situation but, mainly, direct the future dimensions for the development of research. Conceptual representations contribute decisively, not only to the development of the perception of the action of language or thought [26] but in recent years they have contributed very strongly to the development and evolution of computer technology as well [8].…”
Section: Introductionmentioning
confidence: 99%